FAMILY CORETHRELLIDAE - Gil-Azevedo, Leonardo H.; Corrêa, Caio C. D.; Borkent, Art (Zootaxa, 2016)
Corethrellidae are poorly known in Colombia, with few specimens deposited in collections, and only nine named species of Corethrella Coquillett are reported for the country. An additional six undescribed species have been recently collected, indicating that the number of recorded species in Colombia is underestimated.